Numerical Analysis of Heat Transfer Enhancement in Wavy Trapezoidal and Rectangular Microchannels - Hazra, Soumik Kumar (Universitas Mercu Buana, 2025)
This study presents a comprehensive numerical investigation of heat transfer enhancement in microchannels with varying geometries, specifically focusing on wavy microchannels with trapezoidal and rectangular cross-sections. Water is used as the working fluid, and silicon is selected as the solid wall material. A three-dimensional conjugate heat transfer model is developed by solving the steady-state Navier–Stokes and energy equations using the finite volume method in ANSYS Fluent, with the SIMPLEC algorithm employed for pressure–velocity coupling. The analysis examines the influence of cross-sectional shape and wall waviness on thermal performance, while maintaining a constant hydraulic diameter across all configurations. Eight different geometries, including smooth and wavy versions of rectangular and trapezoidal cross-sections with varying top-to-bottom width ratios (0.075–0.055 mm), are evaluated over a Reynolds number range corresponding to inlet velocities of 0.5–4.0 m/s. Results show that wavy microchannels significantly enhance heat transfer compared to their smooth counterparts. For instance, at 4 m/s, the Nusselt number for the wavy rectangular microchannel reaches 9.48, compared to 7.19 for the smooth rectangular configuration, representing a 32% enhancement. Similarly, the wavy trapezoidal channel with a top width of 0.18 mm achieves a maximum Nusselt number of 9.25, compared to 7.19 for its smooth equivalent, indicating a 29% improvement. Additionally, the Nu/Nu₀ versus Re plots reveal a consistent trend of increased heat transfer due to wall waviness across all geometries, with negligible influence from cross-sectional shape when hydraulic diameter is kept constant. The study demonstrates that incorporating wavy structures into microchannel designs significantly improves thermal performance with minimal increases in pressure drop, and that the effect is driven more by wall geometry than by cross-sectional shape. These findings provide valuable insights for the development of compact and efficient microchannel heat sinks for electronic cooling applications.